The Genesis of the Turkish Model - Umbreen Javaid; Fatima Waqi Sajjad (Journal of Political Studies, 2015)
The term Turkish model first appeared in the news media during the post cold war days when the newly independent Muslim Turk Central Asian Republics sought to carve a new identity for themselves in a new era. Later the term became popular during the Arab Spring when the revolting Arabs saw their prosperous Muslim neighbor as an inspiring example for their future direction. The Western world also endorsed the Turkish model as a viable Muslim democracy for the transforming Middle East. The current paper digs deep into history to trace the roots of the idea of the Turkish model examining the developments in the late Ottoman period when Turks’ response to Western modernity set a unique example in the Muslim world. At the same time it created tension between traditional and modern, profound and superficial, authority and freedom ; the conflicts which follow Turkey up to this day and which continue to define the shape of the Turkish Model.